Sex differences in schizophrenia: symptomatology, treatment efficacy and adverse effects - Ivi Moniem; Vasilios Kafetzopoulos (Frontiers in Psychiatry)
IntroductionThis systematic review highlights that schizophrenia (SZ) manifests significant sex differences across neurobiological, clinical, treatment response, and adverse effect domains, underscoring the need for sex-specific considerations in both research and clinical practice.MethodsA systematic search was conducted following PRISMA guidelines, primarily through Pubmed, PsycINFO, Web of Science, and the Cochrane Library. Eligible studies on sex differences in patients with schizophrenia were included. Main search keywords were schizophrenia, sex differences, sex, gender, neurobiology, symptomatology, epidemiology, treatment response, adverse effects.ResultsWhile lifetime prevalence is similar between men and women, the disorder’s trajectory diverges. Men typically experience illness onset approximately 3–5 years earlier than women, with more severe negative symptoms, worse social functioning, and higher rates of comorbid substance use disorders. By contrast, women often have later onset—including a secondary mid-life peak likely linked to declining estrogen—and tend to present with more affective symptoms. Neurobiologically, men with SZ exhibit more extensive structural brain abnormalities and cognitive impairment (especially in memory), whereas women benefit from a degree of neuroprotection possibly mediated by estrogen and distinct gene expression patterns. Hormonal influences appear pivotal, with estrogen’s neuroprotective effects potentially delaying onset and mitigating symptom severity in women, and low testosterone levels correlating with more pronounced negative symptoms in men. Treatment response also varies by sex: women with SZ generally respond to antipsychotics at lower doses with better clinical improvement and fewer relapses, whereas men often require higher doses due to faster drug metabolism and also typically face higher relapse risks. Notably, the treatment advantage of women diminishes after menopause. Adverse effect profiles differ as well: women with SZ are more prone to side effects such as antipsychotic-induced hyperprolactinemia, weight gain, and metabolic or cardiovascular complications, while men tend to experience more neurological side effects while also exhibiting lower treatment adherence.DiscussionThese multidimensional sex differences underscore that all aspects of schizophrenia—from pathophysiology and presentation to therapy and side effect management—must be viewed through a sex-specific lens. Tailoring interventions to the needs of men and women patients is essential for optimizing outcomes and advancing personalized care.